Indocyanine Green Fluorescence Plus Blue Dye for Sentinel Lymph Node Biopsy in Patients Undergoing Neoadjuvant Chemotherapy for Breast Cancer: A Multicenter, Prospective Cohort Study - Miao Liu; Yang Yang; Bin Hua; Rui Feng; Tianyu Xu; Mengyuan Wang; Xiaowei Qi; Yingming Cao; Bo Zhou; Fuzhong Tong; Peng Liu; Hongjun Liu; et al. (Thoracic Cancer)
ABSTRACT Background Sentinel lymph node biopsy (SLNB) using radioisotope tracer plus blue dye is the gold standard after neoadjuvant chemotherapy (NAC) in initially cN1 breast cancer patients, but clinical use still has limitations. This study aims to examine diagnostic performance of dual indocyanine green (ICG) and methylene blue tracing for SLNB in patients who have completed NAC for breast cancer with initially cN1 disease. Methods Adult women (20–80 years of age) scheduled to undergo NAC for biopsy‐proven cT0‐3N1M0 primary invasive breast cancer were consecutively enrolled in this prospective, multicenter, cohort study. Upon the completion of NAC, SLNB was conducted using ICG and methylene blue, followed by axillary lymph node dissection. The primary outcome was the detection rate (DR); secondary outcomes included the false‐negative rate (FNR) and adverse events associated with the use of tracers. Results A total of 156 patients were enrolled; all underwent SLNB after NAC. The median number of lymph nodes retrieved during SLNB was 3 (range: 0–11). The DR was 97.4% (152/156; 95% CI, 93.6%–99.0%). The FNR was 6.7% (4/60; 95% CI, 2.6%–15.9%). Negative predictive value was 95.7% (88/92; 95% CI, 89.4%–98.3%). In the subgroup analysis stratified by ycN status, FNR was 4.0% (1/25; 95% CI, 0.7%–19.5%) and 8.6% (3/35; 95% CI, 3.0%–22.4%) in the ycN0 and ycN+ subgroups, respectively. No allergic reaction was reported. Conclusions SLNB with ICG plus methylene blue achieved a high DR and a very low FNR in breast cancer patients with initially cN1 disease. Trial Registration ClinicalTrials.gov (https://www.clinicaltrials.gov/), NCT02869815